PSYCHOLOGICAL AND PEDAGOGICAL SUPPOT FOR FAMILIES WITH DISABLED CHILDREN - Perelygina , I.A. (Modern Psychology, 2021)
The article analyzes and presents the experience of the work of the center for support of children with disabilities "Time of Hope" in Sergiev Posad, Moscow region, which consists of 325 families. The article reveals the essence and content of rehabilitation and health-improving, social-psychological and pedagogical support for families raising children with severe and multiple disabilities. Special attention is paid to the development of the educational potential of the family, including: the family atmosphere, the life values of parents, the nature of child-parent relations, the psycho-emotional state of parents. The tasks of the center's specialists are not only correctional and educational orientation of work with children, but also a huge psychological help to overcome the state of frustration and optimize the self- consciousness of parents, to create conditions for their active participation in the upbringing and education of the child, to form a positive attitude to the child and an optimistic view of the future.
Keywords: social support; psychological and pedagogical support of a family; a disabled child; a social model of disability; adaptive environment; inclusion